Will AI accelerate or delay the race to net-zero emissions? - Luers, Amy; Koomey, Jonathan; Masanet, Eric; Gaffney, Owen; Creutzig, Felix; Lavista Ferres, Juan M.; Horvitz, Eric (Nature, 2024)
As artificial intelligence transforms the global economy, researchers need to explore scenarios to assess how it can help, rather than harm, the climate. Artificial intelligence (AI) is already transforming the global economy. Companies are investing hundreds of billions of dollars each year in these technologies. In almost every sector, AI is being used to drive operational efficiencies, manage complexity, provide personalized services and speed up innovation. As AI’s influence on society grows, questions arise about its impact on greenhouse-gas emissions: will its myriad applications help to reduce the world’s carbon footprint or hinder climate progress? The answer will depend on how AI models are developed and operated, and what changes result from their use. And scientists simply don’t know how all that will pan out — a worrying situation when there is so much at stake. Most discussions so far about AI’s environmental consequences have focused on the direct impacts of these computationally intensive technologies — how much energy, water or other resources they consume and the amount of greenhouse gases they generate. But the global repercussions of AI applications for society will be much broader, from transforming health care and education to increasing the efficiency of mining, transportation and agriculture. Such AI-driven changes can lead to indirect effects on emissions, which might be positive or negative. These indirect effects also need to be taken into account, and could vastly exceed those from direct impacts. Assessments of all types of AI impact are urgently needed. Here’s what we know and what we don’t.